FAKTOR SOSIAL EKONOMI KELUARGA: ANALISIS PADA HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Ummah, Nofida Rahmatul; Qodariyah, Niyar Ana; Nurtamam, Mohammad Edy (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study aims to analyze the influence of parents' socioeconomic status on the mathematics learning outcomes of second-grade students at SDN Bilaporah 3. The research employed a qualitative method with a single case study approach. The study population comprised all second-grade students, who were also the research sample, following a saturated sampling technique. The research instruments included interview guidelines and a mathematics learning outcome assessment rubric. Data analysis was conducted through direct interviews with students and the second-grade homeroom teacher, as well as documentation of students’ mathematics learning results. The findings indicate that students from families with better economic conditions tend to have more optimal access to learning resources, receive greater parental support, and achieve higher mathematics learning outcomes. Conversely, students from economically disadvantaged families often face challenges in understanding mathematical concepts due to limited learning facilities and minimal parental assistance. The implications of this study highlight the need for synergy between schools and families in creating an inclusive learning environment, whether through instructional interventions or increased parental involvement in children's education. This study is expected to serve as a foundation for developing more adaptive learning strategies and formulating educational policies that better address disparities in learning access at the elementary school level.